Visual disturbances as a presenting feature of pseudohypoparathyroidism - Rushikesh Maheshwari; Radha P Rani; Rajendra N Prasad; Karthik T. S. Reddy; Amaresh P Reddy (Indian Journal of Endocrinology and Metabolism, 2013)
Introduction: Visual disturbance as a presenting feature of pseudohypoparathyroidism (PHP) is uncommon. Although papilledema is commonly reported with hypoparathyroidism primary or secondary, but not reported commonly with PHP. Description of the Case: A 10-year-old male child presented to our outpatient service with the complaints of blurring of vision, diplopia, and associated headache. There was no history of seizure episode. Patient had rounded face with a short, stocky built. Shortening of the fourth metacarpal and fifth metatarsal was present. Pitted nails and bilateral cataract. Patient also had clinical signs and biochemical parameters of hypocalcemia, along with normal parathyroid hormone (PTH) levels. Consistent with pseudohypopathyroidism. Conclusion: In cases of chronic papilledema, the assessment of the calcium serum level is a safe and simple method to exclude hypoparathyroidism or PHP.